Rencana Pembangunan Gedung Olahraga (GOR) Badminton di Kawasan Universitas Bangka Belitung Proposal Proyek - Andini, Andini; Macela Putri, Disti; Fernando, Eric; Dezta Maharani, Nuraprillia; Samsuddin, M. Afdal (PENG: Jurnal Ekonomi dan Manajemen, 2025)
Development takes place to improve the welfare of local communities. As a developing country, the Indonesia government is focusing on infrastructure development. The Indonesia government considers the development of physical infrastructure to be a key area to achieve equality and high economic growth. Increased infrastructure development is excepted to boost Indonesia’s economic growth. The purpose of this article is to determine the impact of infrastructure development on economic growth in Indonesia. The method used to write this article was to review the literature presented in the form of a narrative and read various news sources presented in a narrative explaining the impact of infrastructure development on economic growth in Indonesia is. The conclusion is 1). Progress in infrastructure development will promote economic growth in indonesia. The increase in infrastructure development is reflected in the increase in the road index, which is one if the main indicators, in line with the efforts of the Indonesia government to continue building roads within the Indonesian terriotory in recent years, indicating that roads make a positive contribution to the development of society. Doing this increase in gross domestic product. Products that serve as indicators of economic growth in indoensia 2). Indonesia’s economic growth is accompanied by increased economic equality. Increased economic growth is reflected in a significant increase in gross domestic product (GDP) and increased economic equality, which is reflected in a key indicator growth in per capita income.